PERANCANGAN SISTEM INFORMASI PENJUALAN KENDARAAN DI DEALER SHOWROOM PT. SUMBER BARU ANEKA MOBIL - Diantoro, Karno; Rahman, M. Gifariz Fradhana (TEKNOFILE : Jurnal Sistem Informasi, 2025)
Sumber  Baru Aneka Mobil is a PT engaged in the sale  of new Suzuki cars in  cash or credit. Sumber Baru Aneka  Mobil has a problem with the Car Sales Information System. The problems faced in facing this era of  the free trade, it is not suprising  that the demands of the rapid  development of the bussiness world and technology must be adapted as optimally as possible. This needs to be  supported  by the avaliabillity of a fast information system so that it can support decision making in the company. Therefore the system created is a new system that solves the problem of car sales at PT Sumber Baru Aneka Mobil. The system that will be proposed is a sales information system using a computer application. The system is a very good alternative to overcome problems that often occur in a system that demands speed. With this system, the administation and payemt section of PT Sumber Baru Aneka Mobil is expected to be able to reduce the presentation of errors and data loss, and smooth the car sales  process at PT Sumber Baru Aneka Mobil.